Formulación de un modelo de ingeniería para la gestión integral del fluido base aceite en el campo Castilla como alternativa al fluido base agua en la sección de 12 ¼” (2019)
The objective of this degree work is to formulate an engineering model for the integral management of the oil-based fluid in the Castilla Field as an alternative to the water-based fluid in the 12 ¼ ”section, especially in Operational Unit E3 and E4, for which the advantages and disadvantages of each of the proposed fluids are analyzed in comparison with the fluid that is currently being used in said field, taking into account the formation properties, the evaluation of an oil-based drilling fluid is proposed. of emulsion used successfully in the operations of the Cupiagua Field with the purpose of replacing the water-based fluid system and generating operational advantages and less long-term costs. It begins with the description of the generalities and geologies of the Castilla Field, in addition to its production history highlighting the Carbonera, León and Guayabo formations. On the other hand, the characteristics of the drilling fluids were described, their functions, properties, and the type of fluid that exists, in this way the efficiency is compared against the relevant problems in the 12 ¼ ”intermediate section of the Field Castile.